P-37 Normalising death and dying: an introduction to hospice care for children. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Lane, Claire; Morris, Rachel; Richardson, Lorna
Abstract : Background: Death and dying are still taboo subjects within British society, and this is particularly true when discussing end-of-life with children (Christ & Christ, 2006; Fearnley & Boland, 2019; McManus & Paul, 2019; Paul, 2016). There is little opportunity for children to gain understanding of palliative care, especially those whose families have not experienced terminal illness (Lawrance & Mitchell, 2018; Paul, Cree & Murray, 2016). A project was designed to link a Liverpool-based hospice and a local secondary school by inviting pupils to spend time with staff and patients in the Day Therapy Unit. Aims: To raise students' awareness of palliative care and the role of the hospice within the community. Methods: Contact was made between the hospice and a local secondary school to arrange a pilot project. The school identified six students to participate based on the students' resilience and maturity. These students attended a session with hospice staff to gain some understanding of palliative care and ask questions within a supportive environment. The students were invited to the Day Therapy Unit weekly to engage with hospice staff and patients in a range of activities. After six weeks the students were invited to run an activity for the patients. Results: Feedback received was overwhelmingly positive. The students enjoyed spending time in the hospice, with one significantly interested in volunteering on a regular basis. The patients and staff were always happy to see the students, engaging them in conversation and encouraging their participation. Conclusions: In the future we plan to engage more students in projects and aim to encourage these students to present their experiences to their peers. We will also look to measure learning objectives both before and after the students' visits. The pilot project has shown that it is possible for children to experience our hospice in a safe and enjoyable manner, therefore gaining greater understanding around palliative care and the role of a hospice.